Effect of primary packaging on microbiological status of oral solid dosage form - Khana, Meenal; Teotia, U. V. S; Siingh, Yogendra (Journal of Applied Pharmaceutical Research, 2018)
The emergence of microbial contaminants in non-sterile drugs caused not only the degradation of many products, but also proved to be a potential risk to consumer health. The aim of this study was to test microbial load of non sterile solid pharmaceutical product and investigate the effects of different packaging system on microbial status of pharmaceutical product. A total of 18 sample of solid dosage form packaged in different packaging were procured from market. All samples have been tested for the presence of specific microorganisms, Total aerobic microbial counts (TAMC) and Total yeast and mold counts (TYMC) using compendial procedures. Out of 18 sample 72.22 % (n=13) had shown microbial growth and only 16 % (n=3) of samples were non-compliant. Sample containing herbal ingredients, were the most heavily contaminated, showing a bacterial load > 104 CFU/g. The result showed that all the tested samples were free from E. coli. There was no significant difference (p>0.05) in microbial load of product packaged in different primary packaging